Levantamento de presença e uso de frutas nativas como alternativa de produção e preservação da biodiversidade no município de Campo Bonito-PR - Pereira, Marco Aurelio (2017)
Modern and large-scale agriculture is increasingly promoting the exclusion of family farmers from rural areas as well as rapid environmental degradation across the globe. In the municipality of Campo Bonito, PR, a microregion of cantuquiriguaçu, these factors of exclusion and inequality between classes and environmental degradation in the agrarian environment are very evident. Therefore, a survey of the presence and use of native fruits in the municipality was carried out, aiming to verify the possibility of its use as an alternative of production to the families and also as a way of encouraging the preservation of biodiversity. The forest formation of the region is the mixed ombrophilous forest, or araucaria forest, one of the biomes belonging to the Atlantic forest, possessing a good diversity of native fruit species suitable for the use of the most varied forms. The development of the work took place in 4 stages, the first one being a dialogue with key informants, in this case technicians of the city hall, to define the community where the surveys would be carried out. After the definition of the locality, 20 families were distributed general questionnaires on the way of production of their units and presence of native fruits. Among the 20 initial families, the five that fit the job profile were selected. Subsequent to the selection of the families, a specific questionnaire on the presence and use of native fruits in their properties was applied to them, raising questions such as number of species, diversity, management, fruiting times, forms of exploitation. All the data obtained were based on farmers' knowledge, through semi-structured dialogues and key informants. After the research, a good knowledge of the families on the native fruits was verified, and a real interest in its use. It is concluded that there is a potential for the use of these species as a resistance to agribusiness, but lack of knowledge and initiatives of public agencies, through their technicians, to improve knowledge and better develop these species in the rural properties of the municipality.